Academic achievement and students’ satisfaction towards inquiry-based learning and gamification of grade 7 students - Pawanrat Khotphat; Prasart Nuangchalerm; Antomi Saregar (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Effective science education should promote not only academic achievement but also student motivation and engagement. Integrating inquiry-based learning with gamification has been suggested as a promising approach to support these outcomes, especially in middle school contexts where students often face challenges in understanding abstract scientific concepts.Aim: This study aims to evaluate the academic achievement and satisfaction of Grade 7 students after learning thermal energy concepts through inquiry-based learning integrated with gamification. The target benchmark was set at 70% achievement to assess the effectiveness of the learning model.Method: A post-test only experimental design was employed with 39 Grade 7 students at Kalasin Pittayasan School. The intervention involved four learning sessions that applied inquiry-based strategies enhanced with gamified activities. Research instruments included lesson plans, a 10-item multiple-choice academic achievement test, and a student satisfaction questionnaire. Data were analyzed using descriptive statistics and one-sample t-tests.Results: Findings revealed that students' average achievement score (73.80%) significantly exceeded the 70% criterion (p < 0.05). Students also reported high satisfaction with the learning experience, citing improved understanding, enjoyment, and motivation. Qualitative feedback highlighted a positive classroom environment, increased willingness to participate, and appreciation for game-based elements.Conclusion: The integration of gamification within inquiry-based learning can effectively enhance both academic performance and learner satisfaction in science education. This approach offers a meaningful instructional model for middle school science classes. Future research should explore its long-term impact and adaptability across different subjects and student populations.